Efektivitas Model Pembelajaran Kooperatif Tipe Jigsaw terhadap Hasil Belajar Matematika dan Sikap Percaya Diri Siswa - Suryadi, Suryadi; Meinarni, Welli; Sukayasa, Sukayasa; Ismaimuza, Dasa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the effectiveness of the application of the jigsaw type cooperative learning model in improving the learning outcomes of class XI MIPA SMAN 1 Tinombo students on inverse matrix material and to determine the effectiveness of the application of the jigsaw type cooperative learning model in increasing the self-confidence of class XI MIPA SMAN 1 Tinombo students. . The method used is True Experimental Design, with a Pretest-posttest Control Group research design. The results of the research showed that there was a significant difference between the increase in students' mathematics learning outcomes in the experimental class and the control class. Meanwhile, regarding students' self-confidence, it was found that there was no significant difference between the increase in students' self-confidence in the experimental class and the control class. The conclusion is that the application of the jigsaw type cooperative learning model is effective in improving mathematics learning outcomes but is not effective in increasing the self-confidence of class XI MIPA students at SMAN 1 Tinombo. Keywords: Confident Attitude, Jigsaw Type Cooperative Learning , Mathematics Learning Outcomes.